The effect of the surgical treatment of brachycephalic obstructive airway syndrome on the thermoregulatory response to exercise in French bulldogs: a pilot study - Žgank, Žiga; Nemec Svete, Alenka; Lenasi, Helena; Vodičar, Janez; Erjavec, Vladimira (Frontiers in Veterinary Science, 2023)
Due to altered anatomy of the upper respiratory tract, brachycephalic dogs exhibit increased airway resistance and reduced surface area for evaporative heat loss, predisposing them to respiratory and thermoregulatory problems, a syndrome referred to as Brachycephalic Obstructive Airway Syndrome (BOAS). Compared to non-brachycephalic dogs, brachycephalic breeds are more susceptible to heatrelated injuries even at low ambient temperatures and relatively low physical activity levels. Surgical treatment alleviates clinical signs, potentially improving dogs' thermoregulatory ability with BOAS.Our study aimed to investigate the thermoregulatory response in French bulldogs. Thirteen dogs were exposed to dynamic exercise on a treadmill and measured the dynamics of their rectal temperature (RT) and heart rate (HR). The experiment was performed in two independent sessions, before and after the surgical treatment. The test consisted of two consecutive five-minute walks at a speed of 2.5 km/h, first at an inclination of 0% and the second at an inclination of 5%, and a 30-min recovery period.Rectal temperature and HR were measured before (t0) the start of the test, at the end of the first (t1) and the second part (t2), and 15 minutes (t3) and 30 minutes (t4) in the recovery. A significant increase in RT and HR was observed during exercise and recovery compared to the resting values, implying 2 This is a provisional file, not the final typeset article that the exercise intensity was sufficient to challenge the thermoregulatory response. The increase of RT was significantly lower during both parts (t1 p = 0.004; t2 p < 0.001) of exercise after the surgical treatment than before the treatment. Although a trend of lower RT after recovery was observed compared to before the surgery, it did not reach statistical significance. Similarly to RT, the HR was significantly lower during exercise after the first (p = 0.020) and the second part (p = 0.011) of exercise after the surgery compared to before the surgery but did not reach significance in the recovery. Based on the results of our study, it was concluded that surgical treatment of BOAS can improve thermoregulation during exercise in French bulldogs with BOAS.